Comparison of Various Anaesthetic Techniques for Laparoscopic Tubal Ligation- A Prospective Study - Divyakant Parmar; Jigar Panchal; Savita Sharma (Academia Anesthesiologica International, 2019)
Background: Present study was conducted to compare various anaesthetic techniques for laparoscopic tubal ligation using general anaesthesia with intubation, general anaesthesia with mask ventilation and total intravenous anaesthesia.Subjects and Methods: Sixty female patients having age between 20-40 years belonging to ASA grade I undergoing laparoscopic tubal ligation were randomly divided into three groups- Group I (GA with ET intubation), Group II (GA with mask ventilation) and Group III (TIVA with Inj. Propofol). General anaesthesia in group I was induced with Inj. Sodium Pentothal 4-6 mg/kg and Inj. Suxamethonium Chloride 1-2 mg/kg followed by ET intubation. In group II, GA was induced with Inj. Sodium Pentothal 4-6 mg/kg and Group III patients were induced with Inj. Propofol 2mg/kg.Results: There were no significant difference found between 3 groups with regards to age, weight and duration of anaesthesia. The incidence of increase in Heart rate (>20/min) and increase in blood pressure (>11-20 mm Hg) were significantly less in group III. The incidence of PONV was also found less in group III as compared to group I and II.Conclusion: Rapid and smooth induction with good intraoperative hemodynamic stability and decrease in incidence of post-operative nausea and vomiting makes TIVA with Inj. Propofol a better choice.